Conservation of earthen architecture: governmental actions and owners’ practices to preserve Ksar Taghit, Algeria - Tinhinane Bachir-Cherif; Messaoud Aiche; Oussouby Sacko (Conservation Science in Cultural Heritage, 2022)
Earthen architecture, notably the ksour of Saoura in Algeria, offers us architectural and urban jewels, and inspiring lessons of human ingenuity showing how past communities had to adapt to the difficult characteristics of the region and integrate themselves into the sensitive and demanding oasis ecosystem. Ksar Taghit (a fortified oasis village) is an exceptional model of this knowledgeable architecture and an example of resistance to the various natural and anthropic risks it has experienced over time due to the various conservation and enhancement programs and the efforts of its inhabitants to enhance their heritage and open it to visitors. Through this study, based on archival documents, and supported by observations and interviews with various actors and photographs showing the state of the ksar, we intend to present the conservation programs undertaken in the region and the impact of the efforts of the inhabitants on the conservation of this property. This article, which is part of a doctoral thesis in progress, aims to present the impact of supervised rehabilitation and owners’ practices on the conservation of cultural values and the authentic spirit of the place. Going beyond the material aspect of the conservation, the question arises about whether the efforts undertaken are sufficient to make this common heritage operational and dynamic.